Pengembangan Media Augmented Reality Berbantuan Aplikasi Assemblr Edu Pada Materi Sistem Pernapasan Manusia - Nissa Azhzara Septiani; Fitri Anjaswuri Septiani; Rini Sri Indriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Nissa Azhzara Septiani. 037121096. Augmented Reality media is a technology that combines two-dimensional and three-dimensional objects into a real object in real-time to help visualize a material engagingly and make learning more interesting. However, at SDN Cilangkap 5 Depok, the media used is not varied, leading to a lack of motivation among students. Therefore, in the learning process, there is a need for the development of learning media assisted by the Assemblr edu application so that learning becomes more interesting and varied. This research aims to develop and determine the feasibility of Augmented Reality media assisted by the Assemblr edu application on the material of the human respiratory system. This research is a Research and Development (R&D) study using the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The data collection technique in this research uses an instrument sheet in the form of a questionnaire. Product testing was carried out by the media, linguists, lecturer material experts, and teacher material experts. The research results from the media experts showed 96%, linguists 100%, lecturer material experts 92.5%, and teacher material experts 100%, with an average of 97%, which falls into the category of 'very feasible' for implementation. Additionally, based on a limited trial conducted with 30 fifth-grade students, a percentage score of 86.59% was obtained, indicating that the development of Augmented Reality Media Assisted by the Assemblr edu Application on Human Respiratory System material is 'very feasible' to be used in the learning process and can increase students' learning motivation Keywords: Media Augmented Reality, Assemblr edu, Learning Motivation